A Few Remarks on the Poetics of Turbulence in Richard Powers’ Operation Wandering Soul - Jean-Yves Pellegrin (Transatlantica)
In Richard Powers’ Operation Wandering Soul, the conventional linearity of narrative gives way to a type of discontinuity and circularity that is reminiscent of the unpredictable movement of turbulent flows. This paper suggests that such turbulence enacts a new way of writing and reading narrative. Turbulence is always described in the novel as a disruptive force that must be checked or a noise that must be silenced. This imperative, which testifies to narrative’s desire for closure and meaning, may be construed as an index of the way narrative order attempts to subdue all turbulence by covering up its proliferating chaos with perfunctory linearity and cosmetic endings. Such activity turns narrative—and the type of reading it encourages—into some kind of eschatology which Operation Wandering Soul denounces as a lie and a form of escapism. In order to counter their harmful effects, the novel thus sets about disturbing narrative order and our reading habits by turning itself into a turbulent text, modeling its innermost structures on that of nonlinear systems.